2019
DOI: 10.25115/ejrep.v17i48.2166
|View full text |Cite
|
Sign up to set email alerts
|

Do Lions Quest (LQ) workshops have systematic impact on teachers’ social and emotional learning (SEL)? Samples from nine different countries

Abstract: La tendencia global de los nuevos currículos de muchos países de la OCDE indica que las habilidades de interacción social son cada vez más importantes. Los educadores deben comenzar a fomentar el desarrollo de las competencias sociales de los alumnos, lo que requiere el desarrollo de sus propios conocimientos y habilidades. Este estudio investigó el posible cambio en el conocimiento de los docentes, su conocimiento aplicado y su percepción de competencia durante los talleres Lions Quest (LQ). Para medir esto, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…In addition, the development of their students' SEL during Lions Quest (LQ) in Norway will be studied. The present study continues the series of investigations for the development of teachers' SEL through LQ program studies in different countries (usually lasting 2-3 consecutive days) that point out that the goals of the workshops were reached in quite harmonious ways regardless of the culture (Talvio et al, 2016;Talvio et al, 2022;Talvio et al, 2019). In Norway, the program is called "Mitt Valg".…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In addition, the development of their students' SEL during Lions Quest (LQ) in Norway will be studied. The present study continues the series of investigations for the development of teachers' SEL through LQ program studies in different countries (usually lasting 2-3 consecutive days) that point out that the goals of the workshops were reached in quite harmonious ways regardless of the culture (Talvio et al, 2016;Talvio et al, 2022;Talvio et al, 2019). In Norway, the program is called "Mitt Valg".…”
Section: Introductionmentioning
confidence: 71%
“…The results of our previous studies of LQ indicated positive changes in the short term (during the LQ teacher workshop) in teachers' perceived importance of SEL and their sense of competence in implementing it (Talvio et al, 2016;Talvio et al, 2019). The purpose of this study was to investigate the possible benefits of LQ to teachers both in the short and in the long term.…”
Section: Purpose Of the Studymentioning
confidence: 96%
See 1 more Smart Citation
“…In order to establish a supportive relational environment, all actors need to possess adequate socio-emotional skills, as relationships are reciprocal and dynamic (Jennings and Greenberg 2009;St-Amand et al 2017). Explicit interventions that foster those skills should be more widely implemented in schools worldwide and in Austria specifically (see, for example, the program 'Lions Quest', which trains teachers' social and emotional learning that gains in popularity in Austria; Talvio et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lions Quest has also been evaluated in 12 countries outside the United States: Turkey (Gol-Guven, 2017; Talvio et al, 2016); Austria (Matischek-Jauk et al, 2017;Talvio et al, 2017;Talvio et al, 2019); Finland, Japan, and Lithuania (Talvio et al, 2016;Talvio et al, 2019); Serbia, Montenegro, and FYRO Macedonia (Maalouf et al, 2019); Argentina, Australia, Germany, and Italy (Talvio et al, 2019).…”
Section: Implementation Experiencesmentioning
confidence: 99%